ARCHITECTURE OF THE STRATEGIC DEVELOPMENT OF THE FINANCIAL POTENTIAL OF ENTERPRISES - ВERIDZE, Tatiana; BUHRA, Alina; ZHUKOV, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Growing competition and economic instability require business entities to ensure sustainable development, use the most modern management tools. In such conditions, the role of the financial potential of enterprises is significantly increased, which underlies the stability of strategic positions, the ability to resist competitors, and ensure the production of modern products demanded by consumers. The conducted study of the components and their classification within the framework of the architectonics of the strategic development of the financial potential of enterprises made it possible to reveal: the relevance of the issues; to present in formal terms the process of building the architectonics of the strategic development of the financial potential of enterprises; to determine the place of the financial potential of enterprises in the system of strategic management of the enterprise; to apply the main elements of a systemic approach to the study of the issues of the architectonics of the strategic development of the financial potential of enterprises. The generalized conclusions are the basis for further research on fund mechanisms and their implementation in ensuring the strategic development of the financial potential of enterprises. When implementing a strategic decision, it is advisable to apply appropriate control of the activities of the enterprise of the real sector of the economy, which involves identifying deviations of current results from planned ones; carrying out analytical activities to identify influential factors; providing information support by forming and providing reports. The results obtained contribute to a deeper understanding of the mechanisms of formation of financial stability of enterprises, which is a key factor in their long-term competitiveness. The study uses methodological principles of the system-synergetic approach, namely the enterprise is considered as a systemic object that is under the influence of internal and external disturbances. The proposed approach allows taking into account the multi-level interaction of factors that affect financial potential, and to form effective strategies for the development of enterprises in a changing economic environment.
Keywords: architecture; strategy; development; enterprise; financial potential